A New N-methoxypyridone from the Co-Cultivation of Hawaiian Endophytic Fungi Camporesia sambuci FT1061 and Epicoccum sorghinum FT1062 - Li, Chunshun (Molecules, 2017)
A new N-methoxypyridone analog (1), together with four known compounds, was isolated from the co-culture of Hawaiian endophytic fungi Camporesia sambuci FT1061 and Epicoccum sorghinum FT1062. The structure of the new compound was elucidated as 11S-hydroxy-1-methoxyfusaricide (1) by extensive spectroscopic analysis and comparison with the literature. The absolute configuration of 1 was determined by comparison with the experimental and calculated ECD spectra. The absolute configuration of compound 3 was investigated and renamed as (+)-epipyridone by comparison of the optical rotation and CD spectrum with those of 1. The other known compounds were identified as epicoccarine B (2), D8646-2-6 (4), and iso-D8646-2-6 (5). Compounds 4 and 5 showed modest inhibitory activity towards pathogenic fungi. Epicoccarine B (2) inhibited A2780 and TK-10 with an IC(50) value of 22 μM.